Properties of Pellets from Forest and Agricultural Biomass and Their Mixtures - Mariusz Jerzy Stolarski; Michał Krzyżaniak; Ewelina Olba-Zięty (Energies)
Pellets can be produced not only from forest dendromass but also from agricultural dendromass derived from short rotation coppice (SRC) plantations, as well as surplus straw from cereal and oilseed crops. This study aimed to determine the thermophysical properties and elemental composition of 16 types of pellets produced from four types of forest biomass (Scots pine I, alder, beech, and Scots pine II), four types of agricultural biomass (SRC willow, SRC poplar, wheat straw, and rapeseed straw), and eight types of pellets from mixtures of wood biomass and straw. Another aim of the study was to demonstrate which pellet types met the parameters specified in three standards, categorizing pellets into thirteen different classes. As expected, pellets produced from pure Scots pine sawdust exhibited the best quality. The quality of the pellets obtained from mixtures of dendromass and straw deteriorated with an increase in the proportion of cereal straw or rapeseed straw in relation to pure Scots pine sawdust and SRC dendromass. The bulk density of the pellets ranged from 607.9 to 797.5 kg m−3, indicating that all 16 pellet types met the requirements of all six classes of the ISO standard. However, it was determined that four types of pellets (rapeseed, wheat, and two others from biomass mixtures) did not meet the necessary requirements of the Premium and Grade 1 classes. The ash content ranged from 0.44% DM in pellets from pure Scots pine sawdust to 5.00% DM in rapeseed straw pellets. Regarding ash content, only the pellets made from pure Scots pine sawdust met the stringent requirements of the highest classes, A1, Premium, and Grade 1. In contrast, all 16 types of pellets fulfilled the criteria for the lower classes, i.e., Utility and Grade 4. Concerning the nitrogen (N) content, seven types of pellets met the strict standards of classes A1 and Grade 1, while all the pellets satisfied the less rigorous requirements of classes B and Grade 4.